How do Latino immigrants perceive the current sociopolitical context: identifying opportunities to improve immigrant health in the United States - Lee, J., and Zhou, Y. (Journal of Social Policy)
Migration is an important social determinant of health for immigrants in the United States. Increased attention on Latino immigrants in recent years has sparked interest in policies that affect this population. While prior research has assessed the potential health impact of specific immigration policies, there is limited understanding of how the overall sociopolitical context shapes the health of Latino immigrants. This study examines the potential mechanisms that link the sociopolitical context and health among Latino immigrants. Specifically, we explore how perceptions of the sociopolitical context are implicated in this relationship. Qualitative interviews with community gatekeepers (n=13) and Latino immigrants (n=34) in New York City revealed general perceptions about the overall sociopolitical context, which were characterized by discrimination towards immigrants, unpredictable and mercurial circumstances, and confusion and lack of information. These perceptions influenced participants$1 (Bpsycho-emotional health and health-related behaviors. Findings suggest the importance of integrating immigrants$1 (Bperceptions of the sociopolitical context into health promotion efforts. Furthermore, findings demonstrate the need for paradigm shifts in developing policy-related actions to integrate immigrants$1 (Bperspectives. We propose an integrated, multi-level framework to guide future research and practice regarding social determinants of immigrant health. - Reproduceds
Keywords: Health services - United States